Non-periodic locally soluble groups with non-Dedekind locally nilpotent norm of decomposable subgroups - Lyman, F. N.; Lukashova, T. D. (Ukrains’kyi Matematychnyi Zhurnal, 2026)
UDC 512.544We study the relations between the properties of nonperiodic groups and the norms of their decomposable subgroups. The influence of restrictions imposed on the norm of decomposable subgroups and on the properties of the group is analyzed under the condition that this norm is non-Dedekind and locally nilpotent. We also describe the structure of nonperiodic locally soluble groups for which the norm of decomposable subgroups possesses the indicated properties.